The Impact of Design on Healthcare. Restorative Interiors - Silvia Pericu; Chiara Olivastri; Luca Parodi; Sara Iebole (Pad)
As widely recognized, people’s experiences are significantly influenced by their environ- ment, particularly in healthcare settings, which impacts therapeutic outcomes (Galise, 2021). This project proposes a redesign of the Obstetrics department at Santa Croce Hospital in Cuneo, known for high-risk pregnancies and preterm births, through a domestic approach and restorative design improvements that enhance environmental factors. The goal is to humanize hospital environments (Montaccini & Tedesco, 2015) for patients, families, and staff, fostering feelings of welcome and easy access to information. Despite advancements in care, the quality of healthcare facilities often lags behind, even though evidence shows that physical spaces affect mental and emotional health. The project seeks to enhance health, sensory nourishment, and psychological regeneration for patients and medical staff by incorporating materials and forms that evoke nature. Initial interventions included creating homelike spaces with relaxation zones. The redesign prioritizes sensitivity and perception alongside functionality, addressing diverse elements from color schemes to furniture. Stress-exposed individuals require regenerative spaces enhanced by natural elements and light regulation through biophilic design. In the first stage of the ongoing redesign, results from a questionnaire have been shared with staff and patients to evaluate changes in livability and spatial perception. This contribution aims to analyze responses for project advancement while offering critical insights into the limits of light interventions on existing spaces without hindering operational efficiency.